Degeneracja strategiczna polskich przedsiębiorstw - Zelek, Aneta (Degenerated strategic management in Polish companies, 2006)
The article presents the author’s own view on the problem of typical mistakes and failures in Polish strategic management. On the basis of her very deep practical experience as a consultant and researcher, the author formulates specific catalogue of the most popular mistakes and misunderstandings within the process of creating and introducing the business strategies in practice. The most typical situations which can lead to the so-called “strategic degeneration” of Polish companies are as follows: 1) domination of operational problems, 2) misunderstanding of the strategy essentials, 3) incorrect goals formalization process, 4) strategic fetishism, 5) ignoring of strategic diagnosis, 6) syndrome of competitors imitation, 7) inclinations to compete at all costs, 8) un-integrated strategy with the company’s architecture, 9) the lack of innovations, 10) strategic xenophobia.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 332-343